Identification of Seismic Vulnerability in Sleman Regency Based on Site Effect Analysis Using Microtremor Data - El Farsiyyi, Bilqis; Aryono Adhi, Mochamad; Budi Wibowo, Nugroho; Mustami' Limayukha, Desi; Fadlika Widyantari, Elsa; Rahma, Ilqia; Sofyana Ulya, Rahmania (Rekayasa, 2023)
Yogyakarta is a province in the southern part of Java Island which is close to volcanoes. In this area there are sedimentary materials, such as silt, sand, tuff, breccia, agglomerate and conglomerate so that they are at risk of being affected by local site effects when an earthquake occurs. This study aims to determine earthquake vulnerable zones in several areas in Sleman Regency, including Berbah, Kalasan and Prambanan Districts based on site effect analysis with dominant frequency parameters (f0), amplification factor (A0) and seismic vulnerability index (Kg) using micro seismic data with data of 27 points which are then processed using the Horizontal to Vertical Spectral Ratio (HVSR) method and micro zonation using Geographic Information System (GIS). The results of data processing show that the site class in Sleman Regency is divided into 3, namely SD (Medium Soil), SC (Very Dense Soil) and SB (Rock). Areas with rock formations with soft soil structures are the most vulnerable areas to earthquakes. The lowest